2023
DOI: 10.1007/s40137-023-00366-9
|View full text |Cite
|
Sign up to set email alerts
|

Social Media and Apps in Urology

Abstract: Purpose of Review In this study, we aimed to review the common social media (SoMe) apps used and how they have impacted the practice and exchange of information, as well as the challenges of using SoMe in urology. Recent Findings SoMe has become increasingly popular in the urology community. Lay users often turn to SoMe to learn about urological health and share their own experiences, while medical professionals may use it for career development, networking, education, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…It is unclear whether AI carries downsides similar to social media, where men's health research has shown misinformation and poor quality. 2,7,8 ChatGPT can perform diverse physician-oriented tasks, including writing notes, improving empathy in written communications, 1,9 completing certification exams, 10 and simplifying scientific literature. 11 However, there is limited understanding of AI use by patients, who have recently begun turning to new platforms for their health information.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It is unclear whether AI carries downsides similar to social media, where men's health research has shown misinformation and poor quality. 2,7,8 ChatGPT can perform diverse physician-oriented tasks, including writing notes, improving empathy in written communications, 1,9 completing certification exams, 10 and simplifying scientific literature. 11 However, there is limited understanding of AI use by patients, who have recently begun turning to new platforms for their health information.…”
mentioning
confidence: 99%
“…It is unclear whether AI carries downsides similar to social media, where men’s health research has shown misinformation and poor quality. 2,7,8…”
mentioning
confidence: 99%
“…More recently, the advent of the coronavirus disease 2019 (COVID-19) pandemic further increased the digital literacy of both patients and physicians, resulting in an even wider adoption of digital consultations ( 3 , 4 ). Parallelly, new social media platforms such as Instagram or Tik Tok emerged, where significant public attention and interaction are experienced, notwithstanding the partially poor quality and low reliability of the content ( 5 , 6 ).…”
mentioning
confidence: 99%